Identification of Types and Characteristics of Stingless Bee Hives in the Simpur Bee Farm in Kecapi Village - Rudini, Mahmud; Monita, Dwi Niken Kristyanti; Kuswanto, Eko; Listiana, Ika (Biospecies, 2024)
The Simpur Honey Bee Farm is an educational tourism-style bee farm located at the foot of Mount Rajabasa in Kalianda, South Lampung. Stingless bees play a crucial role in plant pollination and environmental conservation. Stingless bees, in protecting themselves, use their bites as a defense against attacks from enemies. This research aims to identify the diversity of stingless bee species and analyze the characteristics of stingless bee hives found in the Simpur Honey Bee Farm in the village of Kecapi. The research method used is exploratory survey. Data collected includes direct observations of bees and the characteristics of stingless bee hives found, collecting bee samples, and identifying them. Stingless bee identification is done through morphological analysis. The results of the research show four species of Stingless Bees in the Simpur Honey Bee Farm area in the village of Kecapi, Kalianda, South Lampung, namely Heterotrigona itama, Lepidotrigona terminata, Tetrigona apicalis, and Geniotrigona thoracica. The characteristics of stingless bee hives are made of resin with divided chambers consisting of entrance doors, honey pots, bee bread pots, and brood cells.